Avaliação do prognóstico em pacientes com carcinoma de mama invasivo e linfonodo sentinela axilar metastático tratadas com e sem linfonodectomia axilar - Ferreira, Vanessa Monteiro Sanvido [UNIFESP] (2020)
Objective: To evaluate the overall survival and locoregional recurrence in patients with sentinel lymph node (SLN) metastatic from breast cancer with or without complete axillary lymph node dissection (ALND). Methods: This is a case-control study evaluated patients with primary invasive breast cancer and clinically negative axilla who underwent lumpectomy and sentinel lymph node dissection (SLND), from February 2008 to December 2018. Patients with metastatic SLN were treated with SLND alone or ALND. Results: A total of 415 patients were included in this study, 23.3% (97 patients) were identified as metastatic SLN, 56 patients were treated with SLND only and 41 patients with ALND. The groups were homogeneous in relation to the variables: age group (50 years versus 51 years and over) (p = 0.279), race (p = 0.120), level of education (p = 0.142), pathological diagnosis (p = 0.210), histological grade (p = 0.983), hormonal receptors (p = 0.708), HER2 status (p = 0.695), pT (p = 0.334). Average age was 58.3 years (SLND) and 56.3 years (ALND), p = 0.456; and average tumor size was 1.8 cm (SLND) and 2.2 cm (ALND), p = 0.048. The ALND group had greater axillary involvement as evidenced by axillary pathological staging, with N1 (73.2%), N2 (19.5%), N3 (4.9%) and SLND group with N1 (62.5%) and no cases N2 or N3 (p <0.001). The 5-year survival was 80.1% in the SLND and 87.5% in the ALND (p = 0.376). The locoregional recurrence was a rare event, average time of 5 years was 1.8% SLND and 7.7% ALND (p = 0.196). Only 4 locoregional recurrences were described and all occurred within 18 months of follow-up. The intraoperative assessment before ACOSOG Z0011 was 90.2% and after ACOSOG Z0011 was 30.8%(p<0,00001). Additionally, the second surgical procedure for ACOSOG Z0011 exclusion criteria occurred only in 3.8% of cases. Conclusions: Overall survival and locoregional recurrence in patients with metastatic axillary sentinel lymph node treated with SLND alone did not differ from those who underwent ALND, corroborating ACOSOG Z0011 data. The omission of axillary lymph node dissection and the implementation of this practice in our service benefited the patients treated with less aggressive surgeries and, potentially, produces lower morbidity.